Spatial Analysis of Potential Fishing Zones (PFZ) for Tuna in Parangtritis Waters Based on Sea Surface Temperature, Chlorophyll-a, and Bathymetry - Raden Mas Cessar Surya Adiputra; Eka Djunarsjah; Fajrun Wahidil Muharram; Andika Permadi Putra (Jurnal Komputer Teknologi Informasi Sistem Komputer (JUKTISI), 2025)
Parangtritis possesses significant fisheries potential, particularly for tuna; however, this potential remains underutilized due to poorly managed information on fishing grounds. This study aims to identify Potential Fishing Zones (PFZ) for tuna in Parangtritis waters based on oceanographic parameters, namely sea surface temperature (SST), chlorophyll-a concentration, and bathymetry. The analysis utilizes MODIS Aqua satellite imagery (July 2021–June 2022) and GEBCO bathymetric data, processed spatiotemporally using Geographic Information Systems (GIS). The results indicate that PFZ were detected only in August, September, and October 2021, as well as April 2022, with a total of 55 identified points. The highest distribution occurred in September 2021, coinciding with chlorophyll-a concentrations reaching 25.378 mg/m³ and SSTs falling within the optimal range of 25.17–25.95°C, conditions that enhance primary productivity and support the base of the tuna food web. The PFZ points were generally located more than 3.5 nautical miles offshore at depths of approximately 100 meters. These findings reveal an ecological relationship among SST, chlorophyll-a, and bathymetry in shaping the habitat preferences of tropical tuna. This approach demonstrates the effectiveness of remote sensing and GIS-based oceanographic data in predicting tuna habitats, supporting small- to medium-scale fisheries, and integrating modern technology with local ecological knowledge.